Paramedic resuscitation competency: A survey of Australian and New Zealand emergency medical services. (16th January 2017) - Dyson, Kylie; Bray, Janet E; Smith, Karen; Bernard, Stephen; Straney, Lahn; Finn, Judith
Abstract: Objective: We have previously established that paramedic exposure to out‐of‐hospital cardiac arrest (OHCA) is relatively rare, therefore clinical exposure cannot be relied on to maintain resuscitation competency. We aimed to identify the current practices within emergency medical services (EMS) for developing and maintaining paramedic resuscitation competency. Methods: We developed and conducted an online cross‐sectional survey of Australian and New Zealand EMS in 2015. The survey was piloted by one EMS and targeted at education managers. Results: A total of nine of the 10 EMS responded to the survey. All EMS reported that they provide resuscitation training to paramedics at the commencement of their employment (median 16 h, interquartile range [IQR]: 7–80). With the exception of one EMS that did not provide any refresher training, a median of 4 h (IQR: 1–7) resuscitation training was provided to paramedics annually. All EMS used cardiac arrest simulations and skill stations to train paramedics. Paramedic exposure to OHCA was not taken into account to determine their training needs. Resuscitation competency was tested by EMS: annually (3/9), biennially (4/9) or not at all (2/9). Two EMS used CPR‐feedback devices in clinical practice and only one EMS regularly performed formal debriefing after OHCA cases. Barriers to resuscitation competency included: difficulty removing paramedics from clinical duties for training and a lack of paramedic exposure to OHCA. Conclusion: All of the surveyed EMS provided initial resuscitation training to paramedics, but competency testing and refresher training practices varied between services. A lack of individual exposure to cardiac arrest and training time were identified as barriers to resuscitation competency.